Alcoholic brain injury is a modifiable risk factor: natural active substance intervention promises to improve alcohol-induced cognitive impairment - Wang, Wenqi; Du, Yuhan; Tong, Xuewen; Liu, Jiahua; Lei, Mingming; Wen, Liankui; He, Yang; Meng, Xinxin; Xu, Xuanwei (Frontiers in Nutrition, 2025)
Alcohol-related brain injury is often manifested as cognitive decline, accompanied by gut microbiota dysbiosis and disruptions in neuroimmune regulation. According to the gut-brain axis theory, natural compounds may alleviate alcohol-induced brain damage by modulating the gut microbiota. This review summarizes the differential vulnerability of various brain regions to alcohol-induced damage and highlights recent advances in the regulatory effects of natural compounds—including polysaccharides, polyphenols, and saponins—on the gut microbiota and its key metabolites, such as short-chain fatty acids (SCFAs), bile acids, and neurotransmitters. Particular attention is given to how these microbiota-mediated changes influence central nervous system function through the “gut-nervous-brain axis,” “gut-immune-brain axis” and “gut-endocrine-brain axis,” especially in regions such as the prefrontal cortex (PFC), central amygdala (CeA), paraventricular nucleus of the hypothalamus (PVH), and parietal cortex (PC). Studies indicate that structurally specific polysaccharides, such as those containing β-(1 → 3)-glucan branches, exert neuroprotective effects by promoting the production of key neuroactive metabolites. This review provides a theoretical basis for the application of gut microbiota-targeting natural products in the prevention and treatment of alcohol-related cognitive disorders and highlights their translational potential in brain health interventions.